A combined strategy of surface markers for sorting immune cell subsets in patients with chronic graft-versus-host disease - DU Yuxuan (Editorial Office of Journal of Third Military Medical University, 2021)
Objective To explore the distribution of immune cell subsets in patients with chronic graft-versus-host disease (cGVHD) and investigate the predictive values of specific cell subsets sorted by surface markers in the development of cGVHD. Methods From October 2020 to July 2021, 58 patients who received hematopoietic stem cell transplantation (HSCT) from the Hematology Medical Center of the Second Affiliated Hospital of the Army Medical University were collected in this study. Flow cytometry was used to detect the ratio of immune cell subpopulations in the cGVHD patients (cGVHD group, n=43) and those without (control group, n=15) who received allogeneic HSCT during the same period. Primary diagnoses of the recruited patients included acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), chronic myeloid leukemia (CML), myelodysplastic syndromes (MDS), severe aplastic anemia (SAA), and β-thalassemia major. The median time to occurrence of cGVHD was 178.5 (47~1 328) d. Peripheral blood (PB) samples were collected for each patient when cGVHD occurred during follow-up or on the day of follow-up during the course of the disease. Results The percentages of PB regulatory T cells (Tregs) and transitional B cells were significantly reduced in the cGVHD group (P < 0.05), and that of CD19+ B lymphocytes was higher than the control group. The percentage of Tregs differed from the cGVHD patients with different severities (P < 0.05). The percentage of Th17-like cells in the patients with moderate cGVHD was significantly higher than patients with mild cGVHD. CD19+ B lymphocytes showed higher percentage in the patients with mild and moderate cGVHD. In the comparison among different targeted organs of cGVHD, only the Tregs percentage was significantly lower in the patients with skin and liver damage than control group, while the percentage of follicular helper T cells in the patients with skin and liver damage was significantly higher than those only having mucous membrane or eye organ involvement. Conclusion Distribution of immune cell subsets after HSCT is an important reference marker for the diagnosis, treatment and prognosis of cGVHD. Treg cells and transitional B cells which are sorted with a special combined strategy of surface markers play specific guiding roles in the pathogenesis, severity and damage of targeted organs of cGVHD.